Development of Student Worksheets by Using the Context of Riau Traditional Houses on Quadrilaterals and Triangles - Astuti Astuti; Zulfah Zulfah; Nur Fitriana (STAI Hubbulwathan Duri, 2022)
This study aims to produce teaching materials in the form of student worksheets by using the context of Riau traditional house on the material of quadrilaterals and triangles for class VII of Junior High School. This developmental research uses Plomp model which consists of a preliminary analysis stage, development stage, and assessment stage. The test subjects in this study were seventh grade students of SMP N 2 Kampar Utara which consisted of 18 students and one mathematics teacher. The subjects of this research were seventh grade students of SMP N 2 Kampar Utara which consisted of 18 students and one Mathematics teacher. The result of this study is to produce student worksheets by using Riau traditional house context on valid, practical, and effective quadrilateral and triangle material.It can be seen that based on the results of the validation of content experts, an average of 3.42 was obtained in the very valid category, the results of the validation of linguists and cultural experts obtained an average of 3.25 which was included in the very valid category.The results of the practicality of student worksheets at the One-to-One and Small Group stages are 87.6% which are included in the very practical category, and the results of the practicality of student worksheets by the teacher are 87.5% in the very practical category. Furthermore, based on the results of effectiveness, it was found that student worksheets using the context of the Riau traditional house were very effective and suitable for use in the classroom.